Penerapan produksi bersih dan penilaian daur hidup industri kecil menengah pengolahan kopi CV. Gunung Betung [Cleaner production implementation and life cycle assessment in a small and medium coffee industry CV Gunung Betung] - Febilian Adiwinata; Suprihatin Suprihatin; Mulyorini Rahayuningsih (Jurnal Teknologi & Industri Hasil Pertanian, 2021)
Coffee is one of Indonesia's leading commodity that has the potential to be developed for agro-industry. High coffee production has encouraged the establishment of a small and medium coffee industry. The purpose of this study is to analyze possible strategies for implementing cleaner production and evaluate the impact on the environment using Life Cycle Assessment (LCA) method with a gate to gate scope. The stages of cleaner production research used quick scan techniques, source identification, cause evaluation and option generation implementation. LCA research stages with the determination of the objectives and scope of research, inventory analysis, environmental impact assessment and implementation of improvements. Greenhouse gases (GHG) emission was assessed as an environmental impact parameter. The results showed the alternative potential for cleaner production that was applied the manufacture of drying domes (Payback Period/PBP) 3.18 months with an investment ofRp. 2,285,000), procurement of generator machines (PBP 1.16 months with an investment of Rp. 5,860,000), making air circulation in roasting room (PBP 0.07 months with an investment of Rp. 1,268,000), making of solid waste composting reactor (PBP 2.18 months with an investment of Rp. 3,440,000) and addition packing equipment (PBP 0.45 month with an investment of Rp. 3.057 .000). The results of the LCA analysis show that 1,000 Kg of dry-processed coffee requires energy of 869.92 MJ and produces GHG emissions of 95.58 Kg CO₂eq / ton coffee fruits or 0.42Kg CO₂eq / Kg coffee powder equal to 2.389Kg CO₂eq/month and 28.674Kg CO₂eq/year.Key words : environmental impact assessment, life cycle assessment, small coffee industries